2018
DOI: 10.1007/s12325-018-0790-1
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Interferon-β1a Does Not Increase the Risk of Stroke in Patients with Multiple Sclerosis: Analysis of Pooled Clinical Trials and Post-Marketing Surveillance

Abstract: IntroductionPrevious studies suggest that multiple sclerosis (MS) patients have a greater stroke risk than the general population but there is limited evidence of stroke risk in patients receiving disease-modifying treatment. We assessed stroke risk in MS patients treated with subcutaneous interferon-β1a (sc IFN-β1a) using pooled data from clinical trials and post-marketing surveillance.MethodsSeventeen phase II–IV Merck KGaA-sponsored trials of sc IFN-β1a were assessed to estimate the stroke incidence rate (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The objective of this investigation was to ascertain the factors that contribute to the hematological irregularities commonly observed in association with these therapies. Several reports have surfaced regarding the incidence of stroke and suboptimal neurological outcomes among patients diagnosed with MS who have undergone alemtuzumab therapy for a minimum of two doses at least 66,67 . They were perhaps linked to hypertension, hence MS patients on alemtuzumab must have frequent arterial pressure monitoring, with special attention paid to increases in systolic BP of more than 20 mmHg, or 20%.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of this investigation was to ascertain the factors that contribute to the hematological irregularities commonly observed in association with these therapies. Several reports have surfaced regarding the incidence of stroke and suboptimal neurological outcomes among patients diagnosed with MS who have undergone alemtuzumab therapy for a minimum of two doses at least 66,67 . They were perhaps linked to hypertension, hence MS patients on alemtuzumab must have frequent arterial pressure monitoring, with special attention paid to increases in systolic BP of more than 20 mmHg, or 20%.…”
Section: Discussionmentioning
confidence: 99%
“…According to existing literature, treatment with subcutaneous interferon beta 1a (IFN-β1a) does not increase the risk of stroke in patients with MS. 31 Muhannad et al reported a case of alemtuzumab-induced simultaneous onset of autoimmune hemolytic anemia, alveolar hemorrhage, nephropathy, and stroke in a 52-year-old man that occurred 8 months after treatment initiation. 32 On the other hand, dimethyl fumarate (DMF) is hypothesized to provide clinical benefit to MS patients in case of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%